2012
DOI: 10.1155/2012/560161
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Output-Only Modal Identification Using Wireless Sensor Network: A Quantitative Field Experimental Study

Abstract: Although significant advancements have been achieved in wireless sensor network (WSN) in the past decades, there is still a strong need for in-depth analysis on wireless time synchronization and data quality during field testing. In this paper, an academic WSN is adopted for output-only modal identification of two full-scale bridges in Xiamen, China. This paper first assesses the accuracy of time synchronization performed by the WSN through a centralized beacon signal and then studies wireless data quality usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…[36] Shen et al applied the normalized cross-correlation function between tethered and wireless sensor data to estimate the relative time lag between them. [37] Bernal assumed the phases of the fundamental mode of structures are identically zero and to synch outputs, he used the time shifts that are needed to modify fundamental mode phase to zero. [38] Zhou et al showed this assumption that the fundamental mode had zero phases is not always correct and suggested a way to find the mode with zero phases beforehand.…”
mentioning
confidence: 99%
“…[36] Shen et al applied the normalized cross-correlation function between tethered and wireless sensor data to estimate the relative time lag between them. [37] Bernal assumed the phases of the fundamental mode of structures are identically zero and to synch outputs, he used the time shifts that are needed to modify fundamental mode phase to zero. [38] Zhou et al showed this assumption that the fundamental mode had zero phases is not always correct and suggested a way to find the mode with zero phases beforehand.…”
mentioning
confidence: 99%